(untitled) (United States, 2010)
This informative anthology provides convenient, inexpensive access to a wide range of current, carefully selected articles from some of the most respected magazines, newspapers, and journals published today. Within the pages of this volume are interesting well-illustrated articles by historians, educators, researchers, and writers, providing an effective and useful perspective on world history from prehistory to 1500. The title is supported by our student website, Dushkin Online. (http://www.dushkin.com/online)
Keywords: World history,Lịch sử thế giới; Periodicals